2016
DOI: 10.2147/ijn.s97207
|View full text |Cite
|
Sign up to set email alerts
|

A new target ligand Ser–Glu for PEPT1-overexpressing cancer imaging

Abstract: Nanoparticles functionalized with active target ligands have been widely used for tumor-specific diagnosis and therapy. The target ligands include antibodies, peptides, proteins, small molecules, and nucleic acid aptamers. Here, we utilize dipeptide Ser–Glu (DIP) as a new ligand to functionalize polymer-based fluorescent nanoparticles (NPs) for pancreatic cancer target imaging. We demonstrate that in the first step, Ser–Glu-conjugated NPs (NPs-DIP) efficiently bind to AsPC-1 and in the following NPs-DIP are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Other previous report also showed that dipeptide Ser-Glu had high specificity to PepT-1, which could act as an active target ligand to functionalize nanoparticles for tumor-targeted drug delivery. 48 Overall, these results confirmed that the active transport by PepT-1 and clathrin-mediated endocytosis might be involved in the cellular uptake of CG-GS-LDH nanocomposites.…”
supporting
confidence: 69%
“…Other previous report also showed that dipeptide Ser-Glu had high specificity to PepT-1, which could act as an active target ligand to functionalize nanoparticles for tumor-targeted drug delivery. 48 Overall, these results confirmed that the active transport by PepT-1 and clathrin-mediated endocytosis might be involved in the cellular uptake of CG-GS-LDH nanocomposites.…”
supporting
confidence: 69%
“…Numerous rodent models have contributed to the understanding of PDAC pathogenesis and thereby, provided opportunities to characterize and detect disease progression from benign to malignant stages with imaging tools. AsPC-1, 105,115 BxPC-3, 47,92,113 Capan-1, 117 Capan-2, 102,110,120 COLO-357, 94,97 MIA PaCa-2, 74,106 Panc-1 95,129 and PL45 cells 108 (KPC) 89,124 and Pdx-1-Cre; LSL-Kras G12D/+ ; Ink4a/Arf −/− . 16,[71][72][73]104 Last mentioned model has been utilized in molecular ultrasound imaging due to the expression of Thy1 or VEGFR2 on its tumor neovasculature.…”
Section: Preclinical Models For Pdac and Pancreatitis Differentiatimentioning
confidence: 99%
“…With the aim of producing high fidelity, preclinical models representative of the architectural and functional complexity of human PDAC, various mouse models including carcinogen-induced and genetically engineered murine pancreatic tumor models have been currently employed for preclinical ultrasound imaging researches. AsPC-1, 105,115 BxPC-3, 47,92,113 Capan-1, 117 Capan-2, 102,110,120 COLO-357, 94,97 MIA PaCa-2, 74,106 Panc-1 95,129 and PL45 cells 108 Compared to the CDX models, PDXs are created by transplanting a piece of patient tumor tissue derived from surgical resection or from tumor biopsies, in immunodeficient mice. 90 Such tissues can be obtained during EUS-FNA.…”
Section: Pdac Mouse Modelsmentioning
confidence: 99%
“…Along with other prodrug targeted transporters, such as the organic anion transporter (OAT) family and the organic cation transporter (OCT) family, the PepT1 transporter is predominately expressed on the apical membrane of enterocytes and its biochemistry, biology, pharmacokinetics and substrate specificity have been well characterized [1923]. As such, PepT1 is a potential drug design target for improving intestinal absorption and the systemic availability of poorly absorbed drug molecules [4,24,25]. In addition to increasing oral drug absorption, an essential step is the conversion of prodrug to its active therapeutic moiety.…”
Section: Introductionmentioning
confidence: 99%